THE INFLUENCE OF WORK ENVIRONMENT AND WORK COMPETENCE ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE AT PT XYZ BATAM - Lasmana, Indra Wahyu (Universitas Negeri Yogyakarta, 2023)
This research aims to determine the influence of the work environment and work competency on employee performance with job satisfaction as an intervening variable in the marketing department of PT. XYZ Batam. The population in this study was 85 employees. Primary data was collected using a questionnaire as an instrument to prove the research results. To test the hypothesis in this research, path analysis was carried out in two stages. The sampling technique chosen was the census method (85 PT employees. The research results showed that: The work environment has a positive and significant influence on the performance of PT employees. Performance at PT. XYZ Batam. 3) The work environment has a positive and significant influence on the performance of PT employees . Performance at PT. XYZ Batam. 3) The work environment has a positive and significant influence on the performance of PT employees. and significant influence on job satisfaction at PT. XYZ Batam. 4) Work competency has a positive and significant influence on job satisfaction at PT. XYZ Batam. 5) Job satisfaction has a positive and significant influence on the performance of PT employees. XYZ Batam. 6) The work environment has no effect on employee performance which is mediated by job satisfaction at PT. XYZ Batam. 7) Work competency has no effect on employee performance which is mediated by job satisfaction at PT. XYZ Batam